Gasdermins in sepsis - Wang, Wenhua; He, Zhihui (Frontiers in Immunology, 2023)
Sepsis is a hyper-heterogeneous syndrome in which the systemic inflammatory response persists throughout the course of the disease and the inflammatory and immune responses are dynamically altered at different pathogenic stages. Gasdermins (GSDMs) proteins are pore-forming executors in the membrane, subsequently mediating the release of pro-inflammatory mediators and inflammatory cell death. With the increasing research on GSDMs proteins and sepsis, it is believed that GSDMs protein are one of the most promising therapeutic targets in sepsis in the future. A more comprehensive and in-depth understanding of the functions of GSDMs proteins in sepsis is important to alleviate the multi-organ dysfunction and reduce sepsis-induced mortality. In this review, we focus on the function of GSDMs proteins, the molecular mechanism of GSDMs involved in sepsis, and the regulatory mechanism of GSDMs-mediated signaling pathways, aiming to provide novel ideas and therapeutic strategies for the diagnosis and treatment of sepsis.